THE ROLE OF SOCIAL NORMS IN THE MORAL RISE OF SOCIETY - Berdikulova Surayyo Aslamovna (Western European Studies, 2023)
Social norms are historically established and accepted rules of behavior in society that regulate relations between people. In this article highlights of the notion social norm, forms, types, functions and role of social norms in the moral rise of society.
Keywords: social norm; society; development; morality